2017
DOI: 10.3390/nu9020173
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Moderate Whole Grain Consumption on Fasting Glucose and Lipids, Gastrointestinal Symptoms, and Microbiota

Abstract: This study was designed to determine if providing wheat, corn, and rice as whole (WG) or refined grains (RG) under free-living conditions will change parameters of health over a six-week intervention in healthy, habitual non-WG consumers. Measurements of body composition, fecal microbiota, fasting blood glucose, total cholesterol, high density lipoprotein (HDL), low density lipoprotein (LDL), and triglycerides were made at baseline and post intervention. Subjects were given adequate servings of either WG or RG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 89 publications
4
27
0
Order By: Relevance
“…At baseline, patients were randomly allocated to two groups to receive dietary advice either to obtain at least half of their cereal servings each day from whole-grain foods (intervention group (n 56)) or from usual cereals (control group (n 56)) for 12 weeks. This time period was designated based on those previous studies showing beneficial effects of whole grains on metabolic markers in 6 and 8 weeks (16,17) . A dietitian met with participants at baseline to explain the 2012 Dietary Guidelines for Americans (9) used in the study and also to provide educational information to facilitate their understanding and adherence.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…At baseline, patients were randomly allocated to two groups to receive dietary advice either to obtain at least half of their cereal servings each day from whole-grain foods (intervention group (n 56)) or from usual cereals (control group (n 56)) for 12 weeks. This time period was designated based on those previous studies showing beneficial effects of whole grains on metabolic markers in 6 and 8 weeks (16,17) . A dietitian met with participants at baseline to explain the 2012 Dietary Guidelines for Americans (9) used in the study and also to provide educational information to facilitate their understanding and adherence.…”
Section: Interventionmentioning
confidence: 99%
“…Similarly, some previous studies have suggested that whole-grain foods may improve glucose and lipid biomarkers in healthy obese or hyperglycaemic adults (14) . Many randomised controlled trials have also evaluated the effects of whole-grain products on blood glucose concentrations and serum lipids, but they have found inconsistent results (15)(16)(17)(18) .…”
mentioning
confidence: 99%
“…They first increase stool mass and decrease transit time, improving digestion and absorption. Fiber and other nondigestible carbohydrates, such as resistant starch, can also be fermented by the commensal microbiota (14). The major end products of this carbohydrate fermentation are short-chain fatty acids (SCFAs), particularly acetate, propionate, and butyrate (52).…”
Section: Fiber Contentmentioning
confidence: 99%
“…There have been several studies that report changes in the gut microbiota following a whole grain intervention. Most studies report only modest to no changes in gut microbiota composition (Cooper et al, 2017).…”
Section: Whole Grainsmentioning
confidence: 99%
“…41 million children under the age of 5 were overweight or obese in 2016. Over 340 million children and adolescents aged [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] were overweight or obese in 2016 (WHO, accessed: January 2019).…”
Section: Introductionmentioning
confidence: 99%